2002
DOI: 10.1017/s0031182001001044
|View full text |Cite
|
Sign up to set email alerts
|

The use of host specificity, pathogenicity, and molecular markers to differentiate between Gyrodactylus salaris Malmberg, 1957 and G. thymalli Zitnan, 1960 (Monogenea: Gyrodactylidae)

Abstract: The validity of Gyrodactylus thymalli has been questioned, based on its morphological and genetic resemblance to G. salaris. This taxonomic problem has practical implications regarding correct diagnosis of G. salaris, which has proved to be highly pathogenic to stocks of wild Norwegian Atlantic salmon. The host specificity and pathogenicity of G. salaris and G. thymalli were experimentally tested on salmon and grayling. Both parasite species were able to infect, live and reproduce on both fish species. G. sala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 0 publications
6
58
0
Order By: Relevance
“…At present, the internal transcribed spacers (ITS1 and ITS2) of nuclear ribosomal RNA genes are the most common molecular marker used to discriminate these parasites (Cunningham 1997;Matìjusová et al 2001Matìjusová et al , 2003Ziêtara et al 2000;Ziêtara and Lumme 2004). The intergenic spacer (IGS) of ribosomal RNA genes have also been tested for G. salaris and G. thymalli , Sterud et al 2002, Hansen et al 2006. The subunit 1 of the mitochondrial cytochrome oxidase (COI) gene may also be used successfully to differentiate species and local Gyrodactylus strains (Meinilä et al 2002(Meinilä et al , 2004Hansen et al 2003Hansen et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the internal transcribed spacers (ITS1 and ITS2) of nuclear ribosomal RNA genes are the most common molecular marker used to discriminate these parasites (Cunningham 1997;Matìjusová et al 2001Matìjusová et al , 2003Ziêtara et al 2000;Ziêtara and Lumme 2004). The intergenic spacer (IGS) of ribosomal RNA genes have also been tested for G. salaris and G. thymalli , Sterud et al 2002, Hansen et al 2006. The subunit 1 of the mitochondrial cytochrome oxidase (COI) gene may also be used successfully to differentiate species and local Gyrodactylus strains (Meinilä et al 2002(Meinilä et al , 2004Hansen et al 2003Hansen et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Sterud et al (2002) found small but consistent differences between G. salaris and G. thymalli in the nucleotide sequences of the intergenic spacer (IGS) of the ribosomal DNA cassette. Surprisingly high levels of intra-and interspecific differentiation of the mitochondrial cytochrome oxidase I gene (CO1) in populations of G. salaris and G. thymalli populations have recently been detected (Hansen et al 2003, Meinilä et al 2004).…”
mentioning
confidence: 96%
“…Morphometric discrimination of G. salaris and G. thymalli is possible using sophisticated statistics (McHugh et al 2000), but this study was based on a limited number of G. thymalli specimens, and on G. salaris specimens that were pooled from several populations across Scandinavia. However, these species have been shown to have different host preferences (Soleng and Bakke 2001, Bakke et al 2002, Sterud et al 2002.…”
mentioning
confidence: 99%
“…This similarity supports the morphological (Žitňan 1960, Ergens 1983, Malmberg 1993, Mo 1994, Denham and Long 1999 and genetic (Cunningham et al 1995b, Zietara and Lumme 2002) similarities reported. However, G. thymalli has a restricted reproduction on salmon (Soleng and Bakke 2001, Bakke et al 2002, Sterud et al 2002), and Shinn et al (2000, using morphology, were able to differentiate G. thymalli from G. salaris, as was Sterud et al (2002) by sequencing the intergenic spacer region (IGS). Of the five populations under study, only the chaetotaxy pattern of G. caledoniensis could be discriminated from the others, but only based on the position of a single sensillum in two different clusters on the dorsal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Each clade was found to be unique in having a different invasion history and pathogenesis to salmon (Bakke et al 2002, Sterud et al 2002. Hence, there is an urgent need to find morphological markers which can readily separate specimens into their respective species and clades.…”
Section: Species Of the Monogenean Genus Gyrodactylusmentioning
confidence: 99%